Third Party ESG Assurance and Capital Costs: Evidence from Indonesia’s Emerging Market - Mindrawati, Deny Nitalia; Romdhon, Mochamad (Indonesian Scientific Publication, 2024)
This study investigates the causal impact of independent ESG assurance on the cost of debt among Indonesian publicly listed firms. With sustainability reporting gaining prominence, the role of third party verification in enhancing credibility and reducing perceived risk remains underexplored, particularly in emerging markets. The objective is to assess whether assurance on ESG disclosures translates into tangible financial benefits. Using a Difference in Differences (DiD) approach, the study analyzes a panel of 253 firm year observations from IDX listed companies between 2020 and 2022. ESG disclosure scores were measured through GRI based content analysis, and assurance was coded as a binary treatment. The primary dependent variable is the cost of debt, calculated as interest expense divided by long term debt. Control variables include firm size, ROA, board independence, and industry classification. Results reveal that ESG assurance adoption significantly reduces the cost of debt, particularly for firms in non heavy polluting industries and those with stronger governance structures. The DiD coefficient indicates a meaningful and statistically significant decline post assurance, suggesting that verified sustainability reports enhance investor and creditor trust. However, assurance does not affect short term profitability, implying its role as a signaling rather than a performance enhancing mechanism. These findings contribute to the literature by offering empirical DiD based evidence on the financial benefits of ESG assurance in emerging markets. The study underscores the strategic importance of third party verification in capital cost management, emphasizing implications for corporate decision making and regulatory policy.